2018 Survey of Journalism & Mass Communication Enrollments. (March 2020) - McLaughlin, Bryan; Gotlieb, Melissa R.; Cummins, R. Glenn
In contrast to previous years, enrollments in journalism and mass communication programs in the United States were relatively stable from 2015 to 2018. Although strategic communication sequences remained the most popular, the percentage of undergraduates enrolled in journalism sequences increased since the previous survey, whereas the percentage enrolled in strategic communication sequences decreased slightly. In addition, the demographic composition of journalism and mass communication programs is changing, as the survey found an increase in the percentage of minority students enrolled in undergraduate and graduate programs. The 2018 survey also revealed growth in online offerings, both at the undergraduate and master's level.